Operational excellence in online food delivery service: the role of food biosafety measures - (:unkn) unknown (Emerald Publishing Limited, 2024)
Purpose: This study explores how food biosafety measures (FBM), electronic service quality and product quality influence consumer satisfaction and loyalty in the online food delivery service (OFDS) sector. It also integrates the technology acceptance mod...
Keywords: Entrega de comida online; Bioseguridad alimentaria